Total Lignans of Schisandra chinensis Ameliorates Aβ(1-42)-Induced Neurodegeneration with Cognitive Impairment in Mice and Primary Mouse Neuronal Cells - Zhao, Xu (PLoS One, 2016)
Lignan compounds extracted from Schisandra chinensis (Turcz.) Baill. have been reported to possess various biological activities, and have potential in the treatment of Alzheimer’s disease. This study was designed to investigate the effects of total lignans of Schisandra chinensis (TLS) on cognitive function and neurodegeneration in the model of AD induced by Aβ(1–42) in vivo and in vitro. It was found that intragastric infusion with TLS (50 and 200 mg/kg) to Aβ(1–42)-induced mice significantly increased the number of avoidances in the shuttle-box test and swimming time in the target quadrant in the Morris water maze test. TLS at dose of 200 mg/kg significantly restored the activities of total antioxidant capacity (T-AOC), as well as the level of malondialdehyde (MDA) both in the hippocampus and cerebral cortex in mice. Results of histopathological examination indicated that TLS noticeably ameliorated the neurodegeneration in the hippocampus in mice. On the other hand, TLS (100 μM) could protect the Aβ(1–42)-induced primary mouse neuronal cells by blocking the decrease of mitochondrial membrane potential (MMP), change the expressions of Bcl-2 (important regulator in the mitochondria apoptosis pathway). Moreover, TLS also decreased the activity of β-secretase 1 (BACE1), crucial protease contributes to the hydrolysis of amyloid precursor protein (APP), and inhibited the expression of JKN/p38, which involved in the MAPKs signaling pathways in both mice and primary mouse neuronal cells. In summary, TLS might protect against cognitive deficits and neurodegeneration by releasing the damage of oxidative stress, inhibiting the expression of BACE1 and the MAPKs inflammatory signaling pathways.